Landscape transformation and economic practices among the first farming societies in Lake Banyoles (Girona, Spain). (October 2014) - Revelles, Jordi; Antolín, Ferran; Berihuete, Marian; Burjachs, Francesc; Buxó, Ramon; Caruso, Laura; López, Oriol; Palomo, Antoni; Piqué, Raquel; Terradas, Xavier
<x content-type="archive" xml:space="preserve">Abstract</x> This paper focuses on the high-resolution pollen analysis of one new pollen record from Lake Banyoles (Girona, Spain) and its contextualisation with other archaeobotanical records (charcoal, seed and wood remains) from the early Neolithic lakeshore settlement of La Draga. Around ca.7250 cal BP, coinciding with the first settlement phase of La Draga, a rapid fall of the pollen values of deciduous Quercus sp. is observed, and a stabilisation of these values is found until ca. 6000 cal BP. The causes for such changes in vegetation cover are discussed, taking into consideration environmental data to calibrate the role of climate in vegetation dynamics, as well as archaeobotanical data to evaluate impact of the management of vegetal resources on the landscape. The discussion of the data shows that climate could not have been the main cause for the decrease of broadleaf deciduous forests, and that the need of gathering raw material for the construction of dwellings played a major role in this change. The fact that these plant community does not recover during the occupation or after the abandonment of La Draga would confirm that human impact continued over time and that forest clearances were maintained for various purposes.